The Growth of MSE: The Effect of Financial Literacy and Access to Finance with Digital Finance and Usage of Digital Technology as Mediators - Zaragoza, Merlin Grace Panggabean; Pramesti, Muthia (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
Abstract. This research was conducted to examine the effect of financial literacy and access to finance on the growth of micro-enterprises in Indonesia, with digital finance and the use of digital technology as mediation. This study uses a quantitative method with Indonesian micro-enterprises as respondents. Sampling obtained a total of 178 respondents, which was carried out by distributing questionnaires to the large community of MSEs: Jakpreneur and BRI Growprenuer. All data that has been collected is processed using the PLS-SEM method. The study results show that financial literacy and access to finance significantly influence the growth of micro-enterprises in Indonesia. The mediating role of digital finance and the usage of digital technology also significantly mediate the relationship between access to finance and micro-enterprise growth. Keywords: Financial literacy, access to finance, business growth, digital financial services, use of digital technology